EFEITO DE GALACTOMANANA DE Leucaena leucocephala (Lam.) de Wit NO METABOLISMO INTESTINAL E NO EPITÉLIO INTESTINAL PARA CONTROLE DE OBESIDADE EM RATOS. - SILVA, Ana Patricia Fontes da (2020)
Objective: To evaluate the effect of L. leucocephala galactomannan (Lam.) From Wit on obesity control in rats fed with sucrose. Methods: Galactomannans were evaluated for monosaccharide composition and viscosity. Twenty male Wistar rats, grouped into: CN (Control), OB (Obese), GG (Guar Gum) and GL (Galactomannan of L. leucocephala) received, for 14 weeks, standard diet or sucrose diet (14%) and 500μl of water (CN and OB) or GG and GL gel per gavage. Weight and consumption were monitored 3 times / week. Laboratory kits were used to measure serum and hepatic blood glucose, triglycerides and cholesterol. Insulin resistance was measured by the TyG Index and oxidative stress by the amount of malondialdehyde. Histological analysis of the intestine was performed with an optical microscope. Results: The M / G ratio of galactomannans was identical (1.5: 1) and the apparent viscosity demonstrated a behavior of non-Newtonian pseudoplastic fluids. Body weight, Lee's index and food consumption did not differ between groups. The OB (7.87 ± 1.2) showed adiposity% higher compared to the CN (4.6 ± 0.6), however the GG (5.86 ± 0.6) and GL (6.14 ± 0, 4) showed a tendency to reduce adiposity. The leucene galactomannan inhibited the development of metabolic changes caused by the consumption of sucrose, including hyperglycemia, since the mean glycemia was CN (85 ± 1.9), OB (102 ± 6.6), GG (90, 5 ± 6.3) and GL (91.25 ± 4.4). The OB group showed an increase in triglycerides (p = 0.02), serum cholesterol (p = 0.003), oxidative stress (p = 0.02) and insulin resistance (p˂0,0001), compared to GG and GL. In addition, the GL group showed a tendency to inhibit TG and hepatic cholesterol. In the intestinal epithelium of the OB, atrophy and shortening of the villi, new vessels and the presence of infiltrated immune cells were observed, evidencing the presence of inflammation in the mucosa. Groups GG and GL did not present histological changes. Conclusion: These data reinforce that the consumption of galactomannan inhibits metabolic changes triggered by predisposing environmental factors, such as the sucrose diet. Becoming a relevant alternative for obesity prevention.